Incidence of Complications in Plastibell Circumcision in Male Infants: Comparison between with and without Coagulation Hemostasis methods - Naima Rasool (Journal of Surgery and Surgical Research - Peertechz Publications, 2017)
Introduction: Circumcision remains the commonest performed surgical procedure in outpatients. Circumcision with Plastibell is the most popular used method of circumcision among surgeons. As any other surgical procedure, it inherits complications, bleeding being the commonest. The aim of this study is to compare the incidence of post-operative complications in circumcision performed with Plastibell with and without coagulation hemostasis in male infants in the outpatient department of Pediatric Surgery, Combined Military Hospital, Lahore. Methods: This study assesses the data of all infants circumcised in outpatient department with Plastibell. All infants were divided in two groups. In Group A, total 170 circumcisions were performed without frenular hemostasis. In Group B, total 193 circumcisions were performed with frenular hemostasis, over the total period of 2 years. Results: Among 170 patients in group A, 30 patients had complication, out of which 28 had bleeding. In group B, after coagulation hemostasis of frenular band, 193 circumcisions were done. Only 2 patients out of 193 had complications. None of them had post circumcision bleeding. Frenular band was found and coagulated in 98 (50.77%) patients. Conclusion: Circumcision with Plastibell in infants is a safe procedure; post circumcision bleeding can be avoided by careful application of Plastibell and dealing with frenular band with coagulation hemostasis.